Elmo's world. Springtime fun! - Dino, Melissa; Parente, Carol-Lynn.; Freudberg, Judy.; Diego, Ken.; Clash, Kevin; Lyon, Rick.; Martin, Jim (Puppeteer); Tartaglia, John, 1978-; Vogel, Matt.; Jeter, Michael; Sesame Workshop; Sony Wonder (Firm) (New York, NY : Sony Wonder, 2002)
Spring is here, and Elmo is celebrating with three B's: birds, bugs and bicycles. With a dancing shade, a mischievous drawer, a frisky television and a playful computer, Elmo's world is a place for preschoolers to learn about the world around them.
Originally produced as three segments for television; released as videorecording on Feb. 12, 2002.
Starring the Sesame Street Muppet Performers: Kevin Clash, Rick Lyon, Jim Martin, John Tartaglia, Matt Vogel, Michael Jeter.
MPAA rating: Not rated.
Also issued on VHS.
DVD; Dolby digital hi-fi stereo.
Closed-captioned.
Keywords: Birds -- Juvenile films; Insects -- Juvenile films; Bicycles -- Juvenile films; Elmo (Fictitious character : Henson) -- Juvenile films; Muppets (Fictitious characters) -- Juvenile films; Films for the hearing impaired; Children's television programs -- United States